1999
DOI: 10.1039/a903773j
|View full text |Cite
|
Sign up to set email alerts
|

First example of the atom transfer radical polymerisation of an acidic monomer: direct synthesis of methacrylic acid copolymers in aqueous media

Abstract: Sodium methacrylate is polymerised directly via atom transfer radical polymerisation (ATRP) in aqueous media using a poly(ethylene oxide)-based macro-initiator; the resulting poly(ethylene oxide-block-sodium methacrylate) copolymers were obtained in good yield and have narrow molecular weight distributions as evidenced by aqueous GPC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
177
1
2

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(184 citation statements)
references
References 12 publications
3
177
1
2
Order By: Relevance
“…30-40%) were relatively high, the final products (at >80% monomer conversion) had a narrow MWD. This report demonstrating that ATRP could be successfully carried out in the presence of water was followed by a communication describing the ATRP of a charged monomer, sodium methacrylate, 318 in aqueous medium at 90°C. The ATRP of a neutral water soluble methacrylate, poly(ethylene oxide) methyl ether methacrylate (MePEOMA), 319 in water was more successful, and it was shown that the reaction was fast even at room temperature (essentially complete monomer conversion within one to several hours).…”
Section: Watermentioning
confidence: 99%
“…30-40%) were relatively high, the final products (at >80% monomer conversion) had a narrow MWD. This report demonstrating that ATRP could be successfully carried out in the presence of water was followed by a communication describing the ATRP of a charged monomer, sodium methacrylate, 318 in aqueous medium at 90°C. The ATRP of a neutral water soluble methacrylate, poly(ethylene oxide) methyl ether methacrylate (MePEOMA), 319 in water was more successful, and it was shown that the reaction was fast even at room temperature (essentially complete monomer conversion within one to several hours).…”
Section: Watermentioning
confidence: 99%
“…functional groups likely to deactivate the catalyst (e.g., acid functions) need to be protected during the polymerization process [238]; ii. achieving a good degree of control in aqueous media is challenging due to the occurrence of several side reactions involving the catalytic system [239].…”
Section: Discussionmentioning
confidence: 99%
“…Near monodisperse poly(methacrylic acid) can be prepared by anionic polymerization of a tertbutyl or benzyl methacrylate followed by a step to hydrolyze the protecting group. ATRP has been shown to polymerize sodium methacrylate directly in water [184]. A homopolymer and a block copolymer, initiated by a PEO macroinitiator, of poly(sodium methacrylate) were produced.…”
Section: Stimuli Responsive Hydrogelsmentioning
confidence: 99%